Gereja Metaverse: Tugas Gereja dalam Pelaksanaan Amanat Agung - Winta Karna; Fibry Jati Nugroho (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The presence of metaverse which is the result of the development of digital technology has been adapted by some churches so that it has given rise to a new model of worship and church, namely the metaverse church. The presence of metaverse technology provides new opportunities and challenges for the church of the future. This research is intended so that the church is able to maximize the implementation of the great commission and the implementation of the church's three tasks by utilizing metaverse technology. This research uses qualitative methods and literature studies. The results of the study revealed a lack of uniformity of opinion among churches regarding the implementation of the great commission in the metaverse world, but the church has the opportunity to optimize service and implementation of the great commission with metaverse technology and the church must prepare itself well to overcome the challenges of the presence of metaverse technology.